A Simple Graphene Modified Electrode for the Determination of Antimony(Iii) in Edible Plants and Beverage - Aguirre-Quintana, M; Aguirre-Quintana, M; Segura-Segura, R; Segura-Segura, R; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Pizarro-Reyes, J; Pizarro-Reyes, J; Flores-Vergara, E; Flores-Vergara, E; Paz de la Vega-Quiroz, A; Paz de la Vega-Quiroz, A; et al. (Elsevier Ltd, 2022)
Antimony(III) is a rare electroactive specie present on Earth, whose concentration is not typically determined. The presence of high concentrations of antimony is responsible for a variety of diseases, which makes it desirable to find convenient and reliable methods for its determination. We have developed a convenient glassy carbon modified electrode with electroreduced graphene oxide GC/rGO for the first time determination of Sb(III) in commercial lettuce, celery, and beverages. The surface of the electrode was characterized by scanning electron microscopy (SEM) and cyclic voltammetry, indicating a heterogeneous and rough surface with a real area of 0.28 cm2, which is ~2.5 times the area of GC. The optimal chemical and electrochemical parameters used were: sodium acetate buffer (pH = 4.3), an accumulation potential of −1.0 V and an accumulation time of 150 s. The analytical validation was developed evaluating the linear range (10–60 µg L−1), limit of detection (2.5 µg L−1), accuracy, repetibility and reproducibility with satisfactory results (relative standard deviation (RSD) values lower than 10%). All the analyzes performed in real samples by stripping voltammetry were compared with GF-AAS, showing statistically similar values, demonstrating that GC/rGO could be effectively applied in the analysis of food samples. © 2021 Elsevier Ltd